2005
DOI: 10.1016/j.jsc.2005.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of theoretical complexities of two methods for computing annihilating ideals of polynomials

Abstract: Let f1, . . . , fp be polynomials in C[x1, . . . , xn] and let D = Dn be the n-th Weyl algebra. We provide upper bounds for the complexity of computing the annihilating ideal of f s = f s1 1 · · · f sp p in D[s] = D[s1, . . . , sp]. These bounds provide an initial explanation on the differences between the running times of the two methods known to obtain the so-called BernsteinSato ideals.Ministerio de Ciencia y Tecnología MTM2004-01165Junta de Andalucía FQM-33

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…. • f m Using the results from [13], which we confirmed through intensive testing (cf. [20]), it follows, that the method by Briançon-Maisonobe is the most effective one for the computation of s-parametric annihilators where f = f 1 .…”
Section: The Annihilator Up To Degree Ksupporting
confidence: 57%
“…. • f m Using the results from [13], which we confirmed through intensive testing (cf. [20]), it follows, that the method by Briançon-Maisonobe is the most effective one for the computation of s-parametric annihilators where f = f 1 .…”
Section: The Annihilator Up To Degree Ksupporting
confidence: 57%
“…Step 1 of this algorithm was given by Oaku and Takayama (1999); one can also use an alternative method introduced by Briançon and Maisonnobe (2002). See also Ucha-Enríquez and Castro-Jiménez (2004), Gago-Vargas et al (2005), and Levandovskyy and Martin Morales (2008). Steps 2 and 3 were introduced by Oaku (1997b, pp.…”
Section: Note Thatmentioning
confidence: 99%
“…Step 1 should be improved by adopting the alternative method of Briançon and Maisonnobe (2002), as was suggested by Ucha-Enríquez and Castro-Jiménez 2004and Gago-Vargas et al (2005). This would require computations in a ring of differential difference operators, which are not yet available with Risa/Asir.…”
mentioning
confidence: 99%
“…Comparing the effectiveness of the algorithms, Gago-Vargas et al (2005) concluded that the method of Briançon-Maisonobe is the best for the computation of s-parametric annihilators. In Levandovskyy and Martín-Morales (2008) we gave experimental results for the case f = f 1 and showed, that the algorithm of Briançon-Maisonobe is faster than the LOT method, which in turn is faster than the algorithm of Oaku and Takayama.…”
Section: Bernstein-sato Ideals Formentioning
confidence: 99%